The Sar1 GTPase is dispensable for COPII-dependent cargo export from the ER - William Kasberg; Peter Luong; Michael G. Hanna; Kayla Minushkin; Annabelle Tsao; Raakhee Shankar; Samuel Block; Anjon Audhya (Cell Reports, 2023)
Summary: Coat protein complex II (COPII) plays an integral role in the packaging of secretory cargoes within membrane-enclosed transport carriers that leave the endoplasmic reticulum (ER) from discrete subdomains. Lipid bilayer remodeling necessary for this process is driven initially by membrane penetration mediated by the Sar1 GTPase and further stabilized by assembly of a multilayered complex of several COPII proteins. However, the relative contributions of these distinct factors to transport carrier formation and protein trafficking remain unclear. Here, we demonstrate that anterograde cargo transport from the ER continues in the absence of Sar1, although the efficiency of this process is dramatically reduced. Specifically, secretory cargoes are retained nearly five times longer at ER subdomains when Sar1 is depleted, but they ultimately remain capable of being translocated to the perinuclear region of cells. Taken together, our findings highlight alternative mechanisms by which COPII promotes transport carrier biogenesis.